ระบบบริหารมหาวิทยาลัยแบบบูรณาการเพื่อส่งเสริมการจัดการธุรกิจเกษตรข้าวอินทรีย์จังหวัดอุตรดิตถ์ - สัตยาภรณ์, สุภาวิณี; จันทร์สี, นภาภรณ์ (Area Based Development Research Journal, 2018)
This study aimed to develop administration system of the university that supports the organic rice agricultural business management, to improve the effectiveness of researchers and area-base research managers, and to synthesize the knowledge and lessons learned for the development of agricultural business management system. The process of knowledge management and system development were connected to Uttaradit Rajabhat University and network of the agriculturists in Uttaradit province. The method of this study was participatory action research and the data were analyzed, using elementary statistics and content analysis. The results showed that Integrative administration system of the university that supports the organic rice agricultural business management in Uttaradit province consisted of engaged administrative system and integrated science. The processes were supported by Integrative Research and University Engagement Center of the Research and Development Institute. The objectives were to develop skills of researchers in identifying problems and developing propositions, to conduct follow-ups, to publish the research findings for public utilizations, to register the achievement factors, and to improve the research continuation. The participants were 96 researchers from 33 sub-projects. The results were related to both main system and support system. The main system was organic rice agricultural business management consisted of 3 subsystems: agriculturalist quality system, value enhancement system, and social business system. The support system of organic rice agricultural business was consisted of 4 subsystems that can be divided into: integrative administration system of the university that supports the organic rice agricultural business management, agricultural business network management system, organic rice database system, and learning, technology, innovation and knowledge development systems. All led to the improvement of organic rice agricultural business management that had its manifestation in the mission integrative system and integrated science. This model of management was connected to the quality assurance systems of the organizations in the network and the improvement of the agricultural business and the development of organic rice marketing both in Thailand and abroad.